Moving Beyond Competition to Collaboration - CGIAR Research Program on Climate Change, Agriculture and Food Security (2013)
Dr. Frank Rijbersman (CEO, CGIAR Consortium) talks about Challenges of Food Security and the Evolution of CGIAR at the Africa Agriculture Science Week (#AASW6) The Forum for Agricultural Research in Africa (FARA) in collaboration with the Government of Ghana will convene the 6th Africa Agriculture Science Week from July 15-19 in Accra, a continental gathering of all stakeholders involved in African agriculture. Learn more: http://www.cgiar.org/calendar-events/ http://www.fara-africa.org/scienceweek/